2015
DOI: 10.5194/os-11-879-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of numerical models by FerryBox and fixed platform in situ data in the southern North Sea

Abstract: Abstract. For understanding and forecasting of hydrodynamics in coastal regions, numerical models have served as an important tool for many years. In order to assess the model performance, we compared simulations to observational data of water temperature and salinity. Observations were available from FerryBox transects in the southern North Sea and, additionally, from a fixed platform of the MARNET network. More detailed analyses have been made at three different stations, located off the English eastern coas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Comparing several models, the authors found a significant difference in a nonlinear effect within the tidal dynamics of the shallow coastal zone, which they attributed in all likelihood to coarse horizontal resolutions. An evaluation [33] of two operational models with relatively high resolutions (up to 900 m) in the North Sea region, BSHcmod v4 and FOAM AMM7 NEMO, found good agreement between the models and observations of the open sea. Near the coast however, the study found a significant deviation between simulated and observed salinity.…”
Section: Introductionmentioning
confidence: 85%
“…Comparing several models, the authors found a significant difference in a nonlinear effect within the tidal dynamics of the shallow coastal zone, which they attributed in all likelihood to coarse horizontal resolutions. An evaluation [33] of two operational models with relatively high resolutions (up to 900 m) in the North Sea region, BSHcmod v4 and FOAM AMM7 NEMO, found good agreement between the models and observations of the open sea. Near the coast however, the study found a significant deviation between simulated and observed salinity.…”
Section: Introductionmentioning
confidence: 85%
“…The recorded variables include temperature, conductivity, salinity (derived from temperature and conductivity), chlorophyll a fluorescence, turbidity, dissolved oxygen (DO), the partial pressure of CO 2 (pCO 2 ), pH, alkalinity, nutrients, and algal groups (derived from patterns of algal fluorescence by excitation at different wavelengths). The data are used for model validation Haller et al, 2015) and assimilation studies Grayek et al, 2011;Fig. 10).…”
Section: Ferryboxmentioning
confidence: 99%
“…comm., May 2020). A past study comparing a FerryBox temperature sensor from a different ship against a fixed buoy found that the ship‐based measurements were on average 0.37°C warmer than the in situ temperatures (Haller et al 2015). While this comparison was performed for a different ship, the FerryBox installation is similar between the two ships so we can assume a similar warming inside the intake pipes of Lysbris Seaways .…”
Section: Resultsmentioning
confidence: 99%